Islamic Religious Education Practice Videos for DevelopingStudent discipline and Gratitude among Elementary School Students - Aisyah Nazwa Listia; Cindy Aulia; Rizky Ramadhani; Zainal Abidin (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) practice videos as a medium for fostering discipline and a sense of gratitude among elementary school students. This study employs a qualitative approach with a descriptive-analytical design through field research methods. The research subjects were PAI teachers and first-grade students at Al-Hakam Elementary School, Bina Insan Lubuk Pakam. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The results indicate that the use of practical videos makes PAI learning more meaningful, contextual, and grounded in real-life experiences. Students not only understand the concepts of discipline and gratitude theoretically but also put them into practice in their daily lives through activities such as making their beds, reciting prayers before and after activities, helping their parents, and expressing gratitude. Practice-video-based learning also enhances students’ engagement, enthusiasm, and active participation. Furthermore, parental involvement in supervising practical video assignments strengthens the continuity of character education between school and home. Research findings indicate that practical videos positively contribute to the development of students’ attitudes toward discipline and gratitude through repeated practice. Thus, PAI practical videos can serve as an alternative learning medium that is contextual, participatory, and oriented toward character development in students from an early age.